Analisis Optimalisasi Penggunaan Aviobridge pada Kelancaran Event Motogp Tahun 2024 oleh Petugas AMC di Bandara Internasional Zainuddin Abdul Madjid Lombok - Wahyuningsih, Putri; Fatmayati, Fryda (Jurnal Manajemen Dirgantara, 2025)
Zainuddin Abdul Madjid Lombok International Airport continues to grow in serving the needs of air transportation in the West Nusa Tenggara region, the airport is one of the main airports in Indonesia that serves as a gateway for local and international tourists. Since the establishment of Lombok as one of the locations for the MotoGP Event at the Mandalika Circuit, the number of passenger arrivals to the airport has increased significantly, especially during the period of the event. This requires the management of airport facilities, especially in the use of supporting facilities such as the aviobridge, to run optimally and be able to support smooth operations during the MotoGP event. In this study, the authors can analyze how AMC officers optimize the use of Aviobridge at the MotoGP Event, and what are the obstacles experienced by AMC officers and AMC officer solutions in overcoming these obstacles. This research was conducted using descriptive qualitative methods. This research was conducted during the 2024 MotoGP event period at Zainuddin Abdul Madjid International Airport Lombok. The research instruments used were primary data and secondary data. The data collection techniques used in this research are Interview, Observasi, and Dokumentation. Based on the results of the study, it shows that the use of the aviobridge during the MotoGP event can run optimally, AMC officers ensure the smooth running of the MotoGP event extra flight by arranging incoming extra flight aircraft slots according to the type of aircraft so that there are no slots that overlap too much and aircraft that cannot use the aviobridge are given parking close to the gate. In addition, AMC officers ensure that the aviobridge is in normal condition, all functions are normal and maintain the cleanliness of the aviobridge so that there are no obstacles when docking or undocking the aviobridge. And AMC officers can handle obstacles that occur during the MotoGP event with solutions that have been provided by AMC officers.